Peta batimetri Danau Sentani Papua - Ervina Indrayani; Kamiso Handoyo Nitimulyo; Suwarno Hadisusanto; Rustadi . (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2015)
Abstract. Lake Sentani is located in Jayapura Regency, Papua Province with an area 9,360 ha and 70-90 meters above sea level. The lake directly adjacent to Cycloops Mountains Nature Reserve, obtaining supplies of about 34 springs. The aim of the research was to describes the lake bathymetry as a basic information for the utilization. The function are as habitat place for many species, water resources, fisheries, transport and tourism. Morphometry and bathymetry of the lake is very important for the sustainable management of the lake functions as a topography and relief lakes that have different extreme depths. Making the bathymetry of the lake is done with the acoustic method. Recording data using Garmin GPSmap 76CSx and Garmin Echo 100 Fishfinder. The result of the research showed that the depth of Lake Sentani with 9 variation at the different location, in generally range 15-23 m. Meanwhile, the waters of the deepest lake located in the eastern part of the lake is more than 70 m and the lowest depths of 0-7 m are in the middle of the Sentani area.Keywords: bathymetry; morphometry; acoustic method; Garmin Echo 100 Fishfinder; Lake SentaniAbstrak. Danau Sentani terletak di Kabupaten Jayapura, Provinsi Papua dengan luas 9.360 ha dan ketinggian 7090 m dpl. Danau ini berbatasan langsung dengan Cagar Alam Pegunungan Cycloops dan memperoleh suplai dari sekitar 34 sumber mata air. Tujuan penelitian ini adalah menggambarkan batimetri danau sebagai informasi dasar pemanfaatan danau. Fungsi danau adalah sebagai habitat makhluk hidup, sumber air masyarakat sekitar, perikanan, transportasi dan pariwisata. Mengetahui morfometri dan batimetri danau sangat penting untuk pengelolaan fungsi danau yang berkelanjutan karena kondisi topografi dan relief danau yang memiliki perbedaan kedalaman ekstrim. Pembuatan batimetri danau dilakukan dengan metode akustik. Perekaman data menggunakan Garmin GPSmap 76CSx dan Garmin Echo 100 Fishfinder. Hasil penelitian menunjukkan bahwa kedalaman perairan Danau Sentani terdiri dari 9 variasi yang umumnya berkisar 1523 m. Perairan danau terdalam berada di wilayah timur danau yaitu lebih dari 70 m dan kedalaman terendah antara 07 m berada di wilayah Sentani tengah.Kata kunci: batimetri; morfometri; metode akustik; Garmin Echo 100 Fishfinder; Danau Sentani